Global growth and distribution: Are China and India reshaping the world? - Maurizio Bussolo; Rafael E. De Hoyos; Denis Medvedev; Dominique Van der Mensbrugghe (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
Over the past 20 years, aggregate measures of global inequality have changed little even if significant structural changes have been observed. High growth rates of China and India lifted millions out of poverty, while the stagnation in many African countries caused them to fall behind. Using the World Bank's LINKAGE global general equilibrium model and the newly developed Global Income Distribution Dynamics (GIDD) tool, this paper assesses the distribution and poverty effects of a scenario where these trends continue in the future. Even by anticipating a deceleration, growth in China and India is a key force behind the expected convergence of per capita incomes at the global level. Millions of Chinese and Indian consumers will enter into a rapidly emerging global middle class—a group of people who can afford, and demand access to, the standards of living previously reserved mainly for the residents of developed countries. Notwithstanding these positive developments, fast growth is often characterized by high urbanization and growing demand for skills, both of which result in a widening of income distribution within countries. These opposing distributional effects highlight the importance of analysing global disparities by taking into account— as the GIDD does—income dynamics between and within countries. – China ; India ; global income distribution ; middle class
Keywords: D58; D31; F16; 330; Wirtschaftswachstum; Makroökonomischer Einfluss; Außenwirtschaft; Gesamtwirtschaftliche Produktion; Einkommensverteilung; Mehr-Sektoren-Modell; China; Indien